Attending to inattention: Identification of deadweight loss under nonsalient taxes. (25th September 2019) - Brusco, Giacomo; Glass, Benjamin
Abstract: Recent developments in behavioral public economics have shown that heterogeneous biases prevent point identification of deadweight loss. We replicate this result for an arbitrary (closed) consumption set, whereas previous results on heterogeneous attention focused on binary choice. We find that one can bound the efficiency costs of taxation based on aggregate features of demand. When individuals have linear demand functions, the bounds for deadweight loss are easy to calculate from linear regressions.